2021
DOI: 10.2147/cmar.s330195
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Clinical Data of Lenvatinib versus Sorafenib for Unresectable Hepatocellular Carcinoma in Italy

Abstract: Background Lenvatinib has been approved in Italy since October 2019 as a first-line therapy for advanced hepatocellular carcinoma (HCC) and to date data on effectiveness and safety of lenvatinib are not available in our region. To fill this gap, we performed a multicentric analysis of the real-world treatment outcomes with the propensity score matching in a cohort of Italian patients with unresectable HCC who were treated with either sorafenib or lenvatinib. Aims and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 20 publications
3
43
0
Order By: Relevance
“…The main toxicities that emerged from the phase III trial were hypertension (42.2%), diarrhea (38.7%), decreased appetite (34.0%), and weight loss (30.9%); PPES was reported by 26.9% of patients versus 52.4% in the group randomized to receive sorafenib (32). In clinical practice, similar adverse events were reported with a high incidence of hypertension, diarrhea, and anorexia/weight loss (33). Monitoring blood pressure and body weight from treatment initiation and educating the patient and his/her caregiver to promptly recognize any problem allow to manage these adverse events as well.…”
Section: Lesson From Thyroid Carcinoma and Hepatocellular Carcinomamentioning
confidence: 87%
“…The main toxicities that emerged from the phase III trial were hypertension (42.2%), diarrhea (38.7%), decreased appetite (34.0%), and weight loss (30.9%); PPES was reported by 26.9% of patients versus 52.4% in the group randomized to receive sorafenib (32). In clinical practice, similar adverse events were reported with a high incidence of hypertension, diarrhea, and anorexia/weight loss (33). Monitoring blood pressure and body weight from treatment initiation and educating the patient and his/her caregiver to promptly recognize any problem allow to manage these adverse events as well.…”
Section: Lesson From Thyroid Carcinoma and Hepatocellular Carcinomamentioning
confidence: 87%
“…Recent real-world data including 466 patients in Italy reported the median PFS as being 9.0 and 4.9 months for the lenvatinib and sorafenib arm, respectively. Patients treated with lenvatinib showed a higher percentage of response rate (29.4% vs. 2.8%; p < 0.00001) compared with those treated with sorafenib [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the cancer stage at the start of TKI therapy was lower in the lenvatinib group than in the sorafenib group. Recent real‐world clinical studies and propensity score matching analysis of aHCC comparing lenvatinib and sorafenib have shown that lenvatinib treatment is more effective 17–19 . In addition, the molecular‐targeted therapy is to start as early as possible for patients who are unsuitable for TACE, although chemotherapy has been formerly introduced only after repeated TACE 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent real‐world clinical studies and propensity score matching analysis of aHCC comparing lenvatinib and sorafenib have shown that lenvatinib treatment is more effective. 17 , 18 , 19 In addition, the molecular‐targeted therapy is to start as early as possible for patients who are unsuitable for TACE, although chemotherapy has been formerly introduced only after repeated TACE. 11 Changes in the position of chemotherapy for HCC over time may be a limitation to the present analysis.…”
Section: Discussionmentioning
confidence: 99%